Enterobacter cloacae Keratitis: Clinicomicrobiological Profiles, Risk Factors, and Outcomes. Issue 9 (12th September 2022) - Rajarajan, Mugundhan; Madduri, Bhagyasree; Mohan, Nitin; Fernandes, Merle
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of the study was to report the clinical features, risk factors, antibiotic susceptibility, and treatment outcomes in a series of Enterobacter cloacae keratitis. Methods: A retrospective analysis was performed of the electronic medical records of microbial keratitis caused by E. cloacae identified by the Vitek 2 system (BioMerieux, Craponne, France). We collected data pertaining to demographics, risk factors, ulcer characteristics, antibiogram, visual acuity at presentation and final follow-up, and management outcome. The main outcome measure was resolution of infection. The final visual acuity was the secondary outcome measure. Results: Ten episodes of E. cloacae keratitis in 9 patients were identified between January 2009 and December 2019. Nine (90%) cases had undergone penetrating keratoplasty and 8 were failed grafts. Other risk factors included topical steroid use and irregular ocular surface due to epithelial bullae. The mean ulcer size was 17.55 ± 13.99 mm 2 . More than 80% of isolates were sensitive to chloramphenicol, gentamicin, and colistin. Nine (90%) cases healed on medical management within 56.55 ± 26.74 days (range 9–120 d), although almost all required adjunctive procedures: tissue adhesive application (n = 6) and/or tarsorrhaphy (n = 4). One case with a near total infiltrate had a mixed infection with Kocuria kristinae requiring therapeutic penetrating keratoplasty. One case developed endophthalmitis and phthisis after the corneal infiltrate resolved. Conclusions: E. cloacae keratitis is a rare clinical entity seen more often in immunocompromised host conditions such as failed corneal transplants with concomitant topical steroids. Most cases healed with medical management.